2022
DOI: 10.3390/fermentation8040187
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Physicochemical, Rheological, Microbiological, and Organoleptic Properties of Synbiotic Ice Cream Produced from Camel Milk Using Black Rice Powder and Lactobacillus acidophilus LA-5

Abstract: Camel milk has become more popular among customers in recent years as a result of its therapeutic effects. In many parts of the world, it is considered one of the primary components of human nutrition. The present study aimed to develop a novel synbiotic ice cream from camel milk formulated with black rice powder (BRP) and investigate the viability of probiotic bacteria (Lactobacillus acidophilus LA-5) during the storage period (60 days). Skim milk powder was replaced by BRP at levels of 0, 25, 50, and 75%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…This is within the acceptable range, and the taste and texture are well received in Tanzanian communities. However, when the pH is higher, it can have detrimental effects on the flavor, texture, and survivability of lactobacilli [69,71,72,78].…”
Section: The Ph Of Yogurt Samplesmentioning
confidence: 99%
“…This is within the acceptable range, and the taste and texture are well received in Tanzanian communities. However, when the pH is higher, it can have detrimental effects on the flavor, texture, and survivability of lactobacilli [69,71,72,78].…”
Section: The Ph Of Yogurt Samplesmentioning
confidence: 99%
“…The outcomes showed that adding BRP to ice cream mixtures significantly increased the overrun, consistency, and melting rate. The findings of the sensory assessment revealed that the treatments that contained 25% BRP are the most preferable ice cream and could be extended to 50% BRP with no detectable alterations (Elkot et al, 2022) [7] . Over a 60-day storage period, the inclusion of BRP enhanced the survivability of Lactobacillus acidophilus LA-5 in the samples of ice cream.…”
Section: Recent Advances In Ice Cream Makingmentioning
confidence: 99%
“…The use of polyphenols has also been shown to have potent antioxidant activity, anti-inflammatory action, and the capability to inhibit the enzymes that are involved in the development of eicosanoids [7,8]. Recently, food producers have shown interest in substitution with synthetic additives (including nutritional and preservative agents, coloring, flavoring, and miscellaneous agents) [9][10][11][12][13] to improve the features of processed foods with natural ones [14][15][16][17][18]. Interestingly, the supplementary antioxidants from natural sources, such as plants, have proven to be efficient in providing protection against oxidative stress due to enzymatic and non-enzymatic elements, some of which are only synthesized in plants and can only be taken in by the body through food [19].…”
Section: Introductionmentioning
confidence: 99%